The Impact of Mangrove Restoration on the Social Economy of the Community of Batu Panjang Village, Rupat Island, Riau Province - Nurmala Berutu; Tumiar Sidauruk; M. Ridha Syafii Damanik; Eni Yuniastuti; M. Farouq Ghazali Matondang (Randwick International of Social Science Journal, 2023)
Mangrove restoration is an effort to restore degraded mangrove ecosystems with the aim of increasing environmental sustainability, biodiversity conservation and providing social and economic benefits for the community. This research aims to determine the extent to which mangrove restoration can influence the socio-economic life of the community in Batu Panjang Village, Bengkalis Regency. The research method used is descriptive qualitative by systematically analyzing and processing data based on the results of observations and interviews with farmer groups, village officials and stakeholders in Batu Panjang Village. The results of this research show that restoration activities provide (1) a positive impact on increasing community knowledge and understanding regarding the function and role of mangroves in coastal area conservation efforts, (2) community empowerment has been carried out by forming a farmer group, namely the Jeram Batu Panjang (JBP) group and the STYA group which plays a role from the land clearing stage, to the planting stage, (3) but has not yet provided/shown a significant impact in increasing income which will affect the social and economic conditions of the community in Batu Panjang Village, Rupat District. This is shown by the research results that the income earned by the community from mangrove restoration activities from the land clearing stage to the planting stage is only around IDR 475,000 on average, still far below the Bengkalis Regency Minimum Wage of IDR 3,599,029.72.